Therapeutic Proteins through Phage Display- A Brilliant Technique for its Simplicity - Krupanidhi, Sreerama (Indian Journal of Pharmaceutical Education and Research, 2019)
Background: Phage Display Technology is an advanced version of rDNA and hybridoma technologies with simplicity in its procedure and production of desired therapeutics and biocontrol products. In this context, the filamentous bacteriophage namely M13 phage was explored by the Nobel Laureates, George P Smith and Gregory P Winter. Due to the unique tolerance of M13 phage to experimental conditions compared to the tailored B-cells, the global bacteriophage mediated pharma market is at its up-surge. In the present mini-review the sequential breakthroughs in the production of therapeutic antibodies and their market potential are explicitly shown. The use of phage for domestic and therapeutic applications needs to be popularized. Materials and Methods: In the present mini review, it is aimed to project the importance of phage display technology over the conventional hybridoma technology. The pertinent literature pertaining to the products of phage display and the scope to enhance the same are considered. Results and Conclusion: Both rDNA technology and hybridoma technology introduced for the first time to the scientific community a tool to design customized monoclonal antibodies using tailored hybrid B-cells and revolutionized medical diagnosis and treatment. They constituted 53% of approved biopharmaceuticals worth billions of US$. They qualify 8th position out of top 10 bestselling pharma products. Alternatively, the emerging technology in pharma industry namely Phage Display for the production of peptides and antibody formats compatible to the host systems came into vogue and revolutionized pharma market and yet to penetrate in Indian pharma industry.
Keywords: Phage Display; M13; George P Smith; Sir Gregory P Winter; Pharma Market